2022
DOI: 10.3390/cancers14225566
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Prospects of [68Ga]Ga-FAPI PET/CT Scans in Lung Cancer

Abstract: Fibroblast activation protein (FAP) could be a promising target for tumor imaging and therapy, as it is expressed in >90% of epithelial cancers. A high level of FAP-expression might be associated with worse prognosis in several cancer types, including lung cancer. FAPI binds this protein and allows for labelling to Gallium-68, as well as several therapeutic radiopharmaceuticals. As FAP is only expressed at insignificant levels in adult normal tissue, FAPI provides a highly specific tumor-marker for many epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Furthermore, the radiolabeled FAP inhibitors applied to PET imaging can potentially monitor therapeutic response to FAP-targeted CAR T-cell therapy, reducing the limitations of CAR T-cell therapy. In addition, the therapeutic effect of CART is also gradually established in HCC and glioblastoma [359][360][361][362][363]. Unfortunately, it has been observed that using FAP-targeted CAR T cells to target subcutaneous tumors in mice led to deadly myelotoxicity and cachexia [224].…”
Section: Targeting Cafs Via Biomarkersmentioning
confidence: 99%
“…Furthermore, the radiolabeled FAP inhibitors applied to PET imaging can potentially monitor therapeutic response to FAP-targeted CAR T-cell therapy, reducing the limitations of CAR T-cell therapy. In addition, the therapeutic effect of CART is also gradually established in HCC and glioblastoma [359][360][361][362][363]. Unfortunately, it has been observed that using FAP-targeted CAR T cells to target subcutaneous tumors in mice led to deadly myelotoxicity and cachexia [224].…”
Section: Targeting Cafs Via Biomarkersmentioning
confidence: 99%
“…Furthermore, the brain, a common site for lung cancer metastasis, exhibits high 18 F-FDG uptake, limiting the effectiveness of contrast agents ( 19 , 20 ). The 68 Ga-FAPI PET/CT has garnered considerable interest for its superior tumor-to-background ratio across various cancers relative to 18 F-FDG PET/CT ( 21 ). Studies comparing these two imaging modalities have demonstrated that 68 Ga-FAPI-04 PET/CT identifies more lesions in NSCLC and achieves greater diagnostic accuracy than 18 F-FDG PET/CT ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…effectiveness of contrast agents(19,20). The 68 Ga-FAPI PET/CT has garnered considerable interest for its superior tumor-tobackground ratio across various cancers relative to 18 F-FDG PET/ CT(21). Studies comparing these two imaging modalities have…”
mentioning
confidence: 99%
“…The utilization of the Gallium-68-labeled fibroblast activation protein inhibitor (68Ga-FAPI) radiotracer, which is a transmembrane peptidase that is upregulated in cancer-associated fibroblasts (CAFs), has the potential to address the difficulty posed by tumors with low 18F-FDG avidity [6,7]. Indeed, several research studies have explored the potential use of 68Ga-FAPI for the detection and assessment of rare malignancies [8,9].…”
Section: Introductionmentioning
confidence: 99%